PENGEMBANGAN BAHASA ANAK USIA DINI MELALUI MENYIMAK DAN MENGUNGKAPKAN KATA DENGAN “GAMBAR BERSERI” - Maarif, Nina Nuriyah; Fajriyah, Nur Indah; Sholichah, Riyadlotus (Atthiflah: Journal of Early Childhood Islamic Education, 2024)
The use of interesting and colorful series of images can help children to concentrate more on learning activities. Serial image media was chosen as the best solution to overcome this problem because serial image media has an important role in clarifying the intention of the storyline, so that children can understand the meaning of the image more youthfully based on the order of the story contained in the image. This study is a quantitative research, which involves numbers, starting from data collection, interpretation of and the data, as well as the appearance of the results. This study uses a saturated sampling technique, because the population is not greater than 30 respondents, namely 21 students of Dharma Wanita Kindergarten School of Sukowati Bungah Gresik Association. This study shows that there is a significant influence with the application of serial images on the ability to listen and express words in group A children at Kindergarten Dharma Wanita Persatuan Bungah Gresik This is shown by the value of sig. (2-Tailed) 0.000 < 0.05. This means that between the variables of the application of serial images to the ability to listen and express words, there is a significant linear relationship. Meanwhile, from the simple linear regression test, the meaning of the influence of the independent variable on the bound variable is 20.3%. It can also be seen from the significance value obtained, which is 0.000 less than 0.05, meaning that H0 is rejected and H1 is accepted, meaning that there is an influence between the series of images on the ability to listen and express words.